Disrupted Reinforcement Signaling in the Orbitofrontal Cortex and Caudate in Youths With Conduct Disorder or Oppositional Defiant Disorder and a High Level of Psychopathic Traits. - Finger, Elizabeth C.; Marsh, Abigail A.; Blair, Karina S.; Reid, Marguerite E.; Sims, Courtney; Ng, Pamela; Pine, Daniel S.; Blair, R. James R. (American Journal of Psychiatry, 2011)
Objective: Dysfunction in the amygdala and orbitofrontal cortex has been reported in youths and adults with psychopathic traits. The specific nature of the functional irregularities within these structures remains poorly understood. The authors used a passive avoidance task to examine the responsiveness of these systems to early stimulus-reinforcement exposure, when prediction errors are greatest and learning maximized, and to reward in youths with psychopathic traits and comparison youths. Method: While performing the passive avoidance learning task, 15 youths with conduct disorder or oppositional defiant disorder plus a high level of psychopathic traits and 15 healthy subjects completed a 3.0-T fMRI scan. Results: Relative to the comparison youths, the youths with a disruptive behavior disorder plus psychopathic traits showed less orbitofrontal responsiveness both to early stimulus-reinforcement exposure and to rewards, as well as less caudate response to early stimulus-reinforcement exposure. There were no group differences in amygdala responsiveness to these two task measures, but amygdala responsiveness throughout the task was lower in the youths with psychopathic traits. Conclusions: Compromised sensitivity to early reinforcement information in the orbitofrontal cortex and caudate and to reward outcome information in the orbitofrontal cortex of youths with conduct disorder or oppositional defiant disorder plus psychopathic traits suggests that the integrated functioning of the amygdala, caudate, and orbitofrontal cortex may be disrupted. This provides a functional neural basis for why such youths are more likely to repeat disadvantageous decisions. New treatment possibilities are raised, as pharmacologic modulations of serotonin and dopamine can affect this form of learning. Reprinted by permission of the publisher.